Pembuatan Silika Gel dari Abu Sekam Padi dengan Pereaksi Asam Kuat dan Asam Lemah dengan Menggunakan Variasi Jumlah Abu Silikat - Muhammad Riza; Fachraniah Fachraniah; Syafruddin Syafruddin (Jurnal Teknologi, 2022)
The Research has been carried out on the making of silica gel from rice husk ash with strong and weak acid reagents using variations in the amount of silicate ash as much as 50, 100, 200 and 300 grams by using hydrochloric acid, nitric acid, acetic acid and citric acid as solvents. This study aims to obtain the effect of the type acid and variations in the amount silicate on the characteristics of silica gel products and as a method of applying adsorption to H2O. The silica gel test resulted from the yield test, water content, ash content, I2 adsorption power, application of adsorption power to H2O and the best product test using FTIR. The more amount of silicate used will affect the quality of silica gel obtained from the results of testing and calculations, optimal result silica gel obtained with amount of silicate ash is 50 grams. The higher amount of silicate ash used, the results obtained will increase. Optimal results obtained from silica gel in hydrochloric acid with the amount of silicate ash 50 grams, where the yield is 17.86%, water content is 4%, ash content is 11% and I2 adsorption power is 1218.24 mg/g. The application of H2O adsorption power is obtained the more amount of silicate used, the higher H2O absorption results. Optimal results obtained from silica gel in hydrochloric acid with the amount of silicate ash 50 grams, where the adsorption power of H2O is 9.6 mL/g. And finally, the best product test using FTIR is hydrochloric acid and nitric acid.